2022
DOI: 10.3390/biomedicines10102574
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Anti-Inflammatory Effects of an Orally Dosed Enzymatically Liberated Fish Oil in a House Dust Model of Allergic Asthma

Abstract: Eosinophils are a major driver of inflammation in a number of human diseases, including asthma. Biologic therapies targeting IL-5 have enabled better control of severe eosinophilic asthma, but no such advances have been made for enhancing the control of moderate asthma. However, a number of moderate asthma sufferers remain troubled by unresolved symptoms, treatment side effects, or both. OmeGo, an enzymatically liberated fish oil, has demonstrated antioxidant and anti-inflammatory properties including the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Further, this cytokine result looks to fit with prior research indicating that fish oil helps the body resolve inflammation rather than suppressing it [21]. Previous research with the OmeGo has demonstrated the reduction of inflammatory mediators associated with type 2 inflammation [16][17][18]. This would be expected to moderate the initial inflammatory response to carrageenan-induced inflammation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Further, this cytokine result looks to fit with prior research indicating that fish oil helps the body resolve inflammation rather than suppressing it [21]. Previous research with the OmeGo has demonstrated the reduction of inflammatory mediators associated with type 2 inflammation [16][17][18]. This would be expected to moderate the initial inflammatory response to carrageenan-induced inflammation.…”
Section: Discussionsupporting
confidence: 80%
“…OmeGo is an enzymatically liberated salmon oil which contains all 21 omegas and fatty acids present in the oil fraction of whole fish. Our previous work has shown OmeGo to have antioxidant and anti-inflammatory properties enabling the reduction in oxidised LDL in healthy human subjects and the attenuation of allergic inflammation in preclinical models [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the anti-inflammatory effects of oleic acid and pentadecanoic acid noted above, OmeGo also contains a lipopeptide fraction composed of microcolins. These originate from blue-green algae, a natural part of the fish's diet, and have been shown to moderate type 2 eosinophilic inflammation, including a reduction in eosinophilic activation and migration and associated reductions in IL-13 levels [20,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the structure included in this review has not been confirmed by Oxagen, but was characterized as OC-459 by Amira. In addition, although Pettipher et al were the first to publish a non-clinical study of OC-459, it appears that the unpublished development of OC-459 had already been undertaken by other parties [ 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Indole-based Potential Gpr44 Analoguesmentioning
confidence: 99%